2018
DOI: 10.17764/1098-4321.61.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Vibration Fatigue Life of Engine Mounted Components

Abstract: As part of the design validation of components mounted on rotating machinery such as a car engine, it is essential to understand the environmental stress in which they operate. In the case of vibration loadings, the reliability must be verified according to accelerated tests that realistically reproduce the in-service stress. Indeed, a representative validation profile permits not only the assessment of the component durability, but also provides a reliable reference for design optimization (downsizing), reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Today, many engine designs are out of preference because they create more noise and vibration than their competitors during normal operation. The general cause of vibrations during the operation of an internal combustion engine is the change in in-cylinder pressure, the noise created by the lubrication gaps between the components, the piston moving up and down, the crank-connecting rod mechanism gaps to which it is connected, and the axial travel gaps in the parts [1,2]. These vibrations of the engine can be described as typical nonstationary motion [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, many engine designs are out of preference because they create more noise and vibration than their competitors during normal operation. The general cause of vibrations during the operation of an internal combustion engine is the change in in-cylinder pressure, the noise created by the lubrication gaps between the components, the piston moving up and down, the crank-connecting rod mechanism gaps to which it is connected, and the axial travel gaps in the parts [1,2]. These vibrations of the engine can be described as typical nonstationary motion [3].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, in which the effects of fuel and oil used in the engine on vibrations were examined, it was observed that the vibrations that occurred during the tests were analysed with two 3-axis accelerometers placed on the crankshaft main bearings [6]. In the literature, it has been determined that the vibration intensity of the engine increases with increasing engine speed and load [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%